Applying Agronomic Principles of Rhizobial Inoculation to the Conservation of a Keystone Legume Species in a High Mountain Ecosystem on an Oceanic Island - Pulido-Suárez, Laura; González-Rodríguez, Águeda M.; Cubas, Jonay; del Arco-Aguilar, Marcelino; Martín-Esquivel, José L.; León-Barrios, Milagros (Frontiers in Agronomy, 2021)
The Teide broom, Spartocytisus supranubius, is an endemism of the Canary Islands (Spain) and the dominant legume of the Tenerife high-mountain ecosystem in Teide National Park (N.P.). Biotic and abiotic stresses are causing a progressive deterioration and decline of the population of this keystone legume. Since its symbiosis with rhizobia is the main nitrogen (N) input into these soils, diminishing the biological nitrogen fixation could compromise the maintenance of this alpine ecosystem. Symbiotically efficient nitrogen-fixing rhizobia have been widely and successfully used as inoculants for agronomic purposes. However, only rarely has rhizobial inoculation been used for legume species conservation in natural ecosystems. In this study, we assessed three Bradyrhizobium sp. strains as inoculants for S. supranubius on seedlings grown in a greenhouse experiment and on juvenile individuals (2-years-old) transplanted on a field trial in the N.P. Plant growth as well as symbiotic and plant physiological parameters were measured to evaluate the effect of rhizobia inoculation. Our results show that broom plants responded positively to the inoculation both in the greenhouse and field trials. The SSUT18 inoculated plants had significantly higher number and weight of nodules, greater sizes (biovolume) and biomass and also showed the highest N which, being not significant in our experimental conditions, it still contributed to more N per planted hectare than control plants, which could be important for the ecosystem maintenance in these N-poor soils. Positive effects of inoculation were also detected on the plant survival rate and water content. The bradyrhizobial inoculation, by accelerating the plant growth can shorten the greenhouse period and by producing more robust juvenile plants, they could help them to cope better with stresses in its natural habitat. Therefore, inoculation with selected rhizobia is a successful strategy to be integrated into conservation campaigns for this threatened legume species.